Desarrollo de un sistema web de publicidad y registro de productos para el emprendimiento lamanense Chocopaxi. - Arteaga Chávez, Nidia Marilú (2021)
This research project aims to develop an advertising web system that facilitates the management of information and optimize the manual processes of the lamanense enterprise that dedicated to the marketing of Chocopaxi products within the canton La Maná, this web system will serve to advertise all products marketed by the lamanense enterprise, in the advertising section you will find real information of the enterprise, link to their official pages, including the WhatsApp number, a description, advertising video, and testimonials of some people who have consumed the product. For the development of the project, the information-gathering phase was carried out with the manager of the venture, to know the current situation, resulting in functional and non-functional requirements that are made up of five modules: general data selection module, customer module, partner module, product module, access module, developed with the Cascade methodology having a sequential systematic approach, which is based on the requirements, analysis, design and testing, to meet the objectives set a comparative analysis of technological tools that allow the construction of the web system was performed, The free software package XAMPP was used, which consists mainly of the MySQL database management system, the Apache web server, and the interpreters for PHP script languages, for the creation of the database the PhpMyAdmin module was used, these tools have allowed the development of the web system together with the Laravel Framework that works with components such as Composer, Artisan, Node js. In conclusion, for the construction of the web system, a requirements analysis made according to the needs of the enterprise, comparative study of the technological tools used in the development through the web system it will be possible to visualize the products and information about the enterprise. There is a module in which the administrator will have access to make the necessary updates.